2010
DOI: 10.1111/j.1439-0523.2009.01682.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci associated with soybean tolerance to low phosphorus stress based on flower and pod abscission

Abstract: Low phosphorus (P) stress limits soybean production. A population of 152 recombinant inbred lines (RILs) derived from a cross between ÔBogaoÕ (P sensitive variety) and ÔNannong 94-156Õ (P tolerant variety) and 248 markers were used to map quantitative trait loci (QTLs) for low-P tolerance. Two pot culture trials were conducted and low-P tolerance evaluated using flower and pod abscission rate under low P and normal P. Conditional QTLs and epistasis for tolerance to low P were also analysed. A conditional QTL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…This is a 70% increase due to the P fertilization. This way, in agreement to other investigations (Zhang et al, 2010;Cruz, Souza Filho, & Pelacani, 2015), soils with low P availability provide lower number of flowers and a higher pod abortion, compromising productivity. In this sense, Batistella Filho, Ferreira, Vieira, and Cruz (2013) also obtained a linear response for soybean pod production in Typic Haplortox up to the maximum test dose of 160 kg ha -1 of P 2 O 5 .…”
Section: B ------------------------------------------F Values -----supporting
confidence: 92%
“…This is a 70% increase due to the P fertilization. This way, in agreement to other investigations (Zhang et al, 2010;Cruz, Souza Filho, & Pelacani, 2015), soils with low P availability provide lower number of flowers and a higher pod abortion, compromising productivity. In this sense, Batistella Filho, Ferreira, Vieira, and Cruz (2013) also obtained a linear response for soybean pod production in Typic Haplortox up to the maximum test dose of 160 kg ha -1 of P 2 O 5 .…”
Section: B ------------------------------------------F Values -----supporting
confidence: 92%
“…Soybean cultivar, NN94-156 (B20), is a low-P tolerance soybean that has been used for linkage mapping in our previous studies, and several QTLs with a high explanation of phenotypic variation have been identified [4,5]. Soybean treatment for phosphorus-deficient and -sufficient conditions were followed as previously described [5,11].…”
Section: Plant Materials and Treatmentmentioning
confidence: 99%
“…Despite great efforts, it remains challenging to pinpoint P-efficiency genes underlying previously identified QTLs that have a relatively large confidence interval. Here, we expanded our previous studies [4,5,9] by conducting a transcriptome analysis of a low-P tolerant Nannong 94-156, under phosphorus-deficient and -sufficient conditions. Our objective was to better understand the genetic and molecular basis of low-P tolerance in soybean.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations